Citizen science initiatives in high-impact weather and disaster risk reduction - Vinnell LJ; Becker JS; Scolobig A; Johnston DM; Tan ML; McLaren L (Massey University)
High-impact weather events cause considerable social and economic harm, with these effects likely to increase as climate change drives extremes and population growth leads to commensurate growth in exposure. As part of the World Meteorological Organization’s World Weather Research Programme, the 10-year High-Impact Weather (HIWeather) Project facilitates global cooperation and collaboration to improve weather prediction, forecasting, and warning. As part of this, the HIWeather Citizen Science Project identifies and promotes activities which involve citizens in the warning value chain, from “sensors” where they passively provide data, through to “collaborators” where they are involved in designing, running, interpreting, and applying the research. As well as benefitting global efforts to reduce societal impacts of weather and other natural hazards, citizen science also encourages hazard awareness and scientific literacy and interest. This editorial introduces the HIWeather Citizen Science Project special issue, summarizing the three papers in this issue in the broader context of high-impact weather and citizen science.
Keywords: citizen science; high-impact weather; earthquakes; disaster risk reduction; 1103 Clinical Sciences; 1702 Cognitive Sciences